Metagenomic insights into the composition and function of the gut microbiota of mice infected with Toxoplasma gondii - Meng, Jin-Xin; Wei, Xin-Yu; Guo, Huanping; Chen, Yu; Wang, Wei; Geng, Hong-Li; Yang, Xing; Jiang, Jiang; Zhang, Xiao-Xuan (Frontiers in Immunology, 2023)
Despite Toxoplasma gondii (T. gondii) infection leading to dysbiosis and enteritis, the function of gut microbiota in toxoplasmosis has not been explored. Here, shotgun metagenomics was employed to characterize the composition and function of mouse microbial community during acute and chronic T. gondii infection, respectively. The results revealed that the diversity of gut bacteria was decreased immediately after T. gondii infection, and was increased with the duration of infection. In addition, T. gondii infection led to gut microbiota dysbiosis both in acute and chronic infection periods. Therein, several signatures, including depression of Firmicutes to Bacteroidetes ratio and infection-enriched Proteobacteria, were observed in the chronic period, which may contribute to aggravated gut inflammation and disease severity. Functional analysis showed that a large amount of KEGG pathways and CAZy family displayed distinct variation in abundance between infected and healthy mice. The lipopolysaccharide biosynthesis related pathways were activated in the chronic infection period, which might lead to immune system imbalance and involve in intestinal inflammation. Moreover, microbial and functional spectrums were more disordered in chronic than acute infection periods, thus implying gut microbiota was more likely to participate in disease process in the chronically infected mice, even exacerbated immunologic derangement and disease progression. Our data indicate that the gut microbiota plays a potentially important role in protecting mice from T. gondii infection, and contributes to better understand the association between gut microbiota and toxoplasmosis.